A systematic review and network meta‐analysis of antimanic drugs for the treatment of acute mania used in Japan. Issue 4 (24th November 2022) - Ishizuka, Kanako; Inada, Toshiya
Abstract: This review aimed to clarify whether antimanic agents used in Japan are superior to placebo for the treatment of acute mania, based on reports of randomized controlled trials (RCTs) conducted in Japan and other East Asian countries. A literature search was conducted using the MEDLINE, PubMed, and Ichushi databases from their dates of inception to July 31, 2021, for studies written in English or Japanese with a primary diagnosis of bipolar I disorder, comparing any of the following active drugs to treat acute mania in adults: aripiprazole, carbamazepine, chlorpromazine, haloperidol, lithium, olanzapine, sultopride, timiperone, and zotepine. A random‐effects network meta‐analysis was performed within a frequentist framework. The quality of each included study was evaluated using the revised Cochrane risk‐of‐bias tool for randomized trials. The outcomes adopted were the response rate for efficacy and dropout rate for tolerability during 3 weeks from baseline. Eleven RCTs, totaling 1148 participants, were reviewed. The pooled odds ratio (OR) (±95% confidence interval [CI]) was calculated. Timiperone (OR = 4.53, CI 1.09–18.80), sultopride (OR = 3.76, CI 1.08–13.05), and aripiprazole (OR = 1.99, CI 1.22–3.24) were significantly more effective than placebo. Olanzapine (OR = 0.51, CI 0.29–0.90) was significantly superior in acceptability to placebo. The results showed no significant differences from placebo for carbamazepine, chlorpromazine, haloperidol, lithium, and olanzapine. These results suggest that noninferiority trials alone cannot always confirm the antimanic drug efficacy and that direct placebo‐controlled trials are necessary to verify the antimanic efficacy of the drugs. Abstract : In Japan, placebo‐controlled trials have only been conducted since 2008. Timiperone, sultopride, and aripiprazole were observed to be significantly more effective than placebo. Direct placebo‐controlled trials, instead of noninferiority trials, are essential to verify drug efficacy.